1982
DOI: 10.1111/j.2153-3490.1982.tb01805.x
|View full text |Cite
|
Sign up to set email alerts
|

Transport of organic carbon to the oceans by rivers of North America: a synthesis of existing data

Abstract: Transport of organic carbon in rivers of North America to the oceans was assessed by compiling and analyzing data from 82 North American rivers draining 60% of Canada and the United States. These data were collected by the U.S. Geological Survey and the Water Resources Branch of Canada's Inland Waters Directorate. Mean annual concentrations of total organic carbon showed considerably less variation than did annual specific export (gC m-2 yr-l).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

1986
1986
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(10 citation statements)
references
References 17 publications
(18 reference statements)
2
8
0
Order By: Relevance
“…At the end of the season, the water flow was relatively constant with DOC concentrations ranging between 1.1 and 1.3 mg L −1 In scaling up the measurements to the 36‐ha watershed, we estimate that 5.25 kg DOC ha −1 was exported from this watershed during the 182‐d study. Yields of DOC measured from conifer biomes in California ranged from 18 to 39 kg DOC ha −1 , California grasslands ranged from 5 to 6 kg DOC ha −1 , while yields from deciduous biomes in other areas ranged from 9 to 28 kg DOC ha −1 (Aitkenhead and McDowell, 2000; Mulholland and Watts, 1982). Thus, it is apparent that a maximum of ∼1% of the 445 kg DOC ha −1 produced from leaching reaches the stream while the rest is either retained by or respired within the soils.…”
Section: Resultsmentioning
confidence: 99%
“…At the end of the season, the water flow was relatively constant with DOC concentrations ranging between 1.1 and 1.3 mg L −1 In scaling up the measurements to the 36‐ha watershed, we estimate that 5.25 kg DOC ha −1 was exported from this watershed during the 182‐d study. Yields of DOC measured from conifer biomes in California ranged from 18 to 39 kg DOC ha −1 , California grasslands ranged from 5 to 6 kg DOC ha −1 , while yields from deciduous biomes in other areas ranged from 9 to 28 kg DOC ha −1 (Aitkenhead and McDowell, 2000; Mulholland and Watts, 1982). Thus, it is apparent that a maximum of ∼1% of the 445 kg DOC ha −1 produced from leaching reaches the stream while the rest is either retained by or respired within the soils.…”
Section: Resultsmentioning
confidence: 99%
“…Many studies have also reported a strong, often positive relationship between DOC and discharge (Mulholland and Watts 1982, Meyer and Tate 1983, Thurman 1985, Eckhardt and Moore 1990, Leenheer 1994), particularly during peak or rising flows (Meyer andTate 1983, Hinton et al 1997). However, stream DOC concentrations can also be inversely related to discharge (Hornberger et al 1995) or completely independent of discharge .…”
Section: How Does the Landscape Influence Differ Between Lacustrine Amentioning
confidence: 99%
“…-The dischargeweighted average concentration of DOC in Bear Brook, -2-3 mg/L, is similar to many other small streams, but on the low end of the range of average DOC concentrations (0.7-28 mg/L) tabulated by Moeller et al (1979) for streams and rivers of the United States. Much of this variability, however, is due to differences in amount of runoff Kuenzler 1979, Mulholland andWatts 1982). Much of this variability, however, is due to differences in amount of runoff Kuenzler 1979, Mulholland andWatts 1982).…”
Section: Organic Chemistry Of Stream Watermentioning
confidence: 99%
“…Fluvial export of DOC has received considerable attention, and has been the subject of several review papers in which global compilations and cross-biome compari-' Manuscript received 15 April 1987;revised and accepted 26 September 1987. sons are made (e.g., Moeller et al 1979, Meybeck 1981, Mulholland and Watts 1982. Fluvial export of DOC has received considerable attention, and has been the subject of several review papers in which global compilations and cross-biome compari-' Manuscript received 15 April 1987;revised and accepted 26 September 1987. sons are made (e.g., Moeller et al 1979, Meybeck 1981, Mulholland and Watts 1982.…”
Section: Introductionmentioning
confidence: 99%